Konsep Pendidikan Nalar Islam dalam Kitab At Tarbiyah Al Aqliyyah Fii Al Qur’an Al Karim - Maduratna, Santi Nariswari (IIQ An Nur Yogyakarta, 2025)
This research will explain the concept of building Islamic reasoning education according to Huda ‘Abdul Rohim Muhammad Qosim Maymani in the book kitab al-tarbiyah al-‘aqliyah fi al Qur’an al-karim. By using content analysis, this research has found that to build Islamic reasoning, several methods are needed, including freeing the mind from all limitations and constraints, as education must indeed be based on freedom if it wants to experience development. Training the senses and conscience as the gateways to reasoning means that educating the mind will not proceed without the presence of the senses and the conscience. Educating the mind in the Qur'an is achieved by pursuing knowledge as the main pathway to educate the mind. Seeking knowledge is the way to acquire various capabilities and is the path taken to educate the mind. Moreover, educating the mind in the Qur'an must be accompanied by enriching thoughts with various kinds of knowledge.